Inflammatory bowel disease and anxiety: links, risks, and challenges faced - Bannaga, Ayman S (Clin Exp Gastroenterol, 2015)
Inflammatory bowel disease (IBD) causes severe physical symptoms and is also associated with psychological comorbidities. Abnormal anxiety levels are found in up to 40% of patients with IBD. Anxiety symptoms are often related to flares of IBD but may persist in times of remission. Detection of anxiety disorder (AD) in patients with IBD can be challenging. Patients with anxiety may also exhibit symptoms in keeping with functional gastrointestinal disorders (FGID). Evidence for the effectiveness of pharmacological and psychological therapies for anxiety stems from patients without IBD. Studies in patients with IBD have either been small or shown negative results. In light of this, a combined approach involving IBD physicians to improve disease control and psychologists or psychiatrists to treat anxiety is advised. This review examines the evidence of anxiety issues in IBD with a focus on extent of the problem, risk factors for anxiety, and the effectiveness of interventions.